SHOCKS, CRISES, AND FALSE ALARMS : HOW TO ASSESS TRUE MACROECONOMIC RISK - Carlsson-Szlezak, Philipp; Swartz, Paul (Harvard Business Review Press, 2024)
"War. Inflation. Recession. Pandemic. The semblance of macroeconomic stability is long gone, with the volatility of recent years challenging leaders and companies to preserve and create value as they navigate the business landscape. When turmoil hits, executives and investors face notoriously unreliable macroeconomic forecasts, whipsawing data, and contradictory opinions. Are disruptions transient and ephemeral-or permanent and structural? False alarms are costly traps, but so are true structural changes that go undetected. Leaders must also assess the doom-laden public macroeconomic discourse, which habitually presents worst-case scenarios as foregone conclusions. How can executives avoid these traps and make better strategic decisions? In this incisive, perspective-shifting book, BCG Global Chief Economist Philipp Carlsson-Szlezak and Senior Economist Paul Swartz provide a fresh and accessible way to analyze and understand the macroeconomy-what they call "regime analysis"-that pushes beyond conventional model-based prediction to emphasize structural context and judgment. Focusing on what it takes for macroeconomic regimes to break, they apply their approach to key risks in the real economy, financial structures, and geopolitical arrangements to help senior executives and investors assess the true risks of their economic context and to build their capacity to respond to changing conditions more effectively. With rational optimism rather than gloom, Shocks, Crises, and False Alarms speaks to the key macro debates and controversies that shape our time, and it empowers leaders with the analytical skills to assess and judge macroeconomic risks for themselves, with a new way of thinking that will continue to apply as risks change over time"--